The effect of leadership style and innovation capital on SMEs sustainability performance from a managerial perspective / Hazlina Hassan … [et al.] - Hassan, Hazlina; Kamaluddin, Amrizah; Saad, Shukriah; Samad, Nurhayati (Universiti Teknologi MARA, 2021)
Small and medium enterprises (SMEs) face various challenges in sustaining their operations in the global business competition. In line with the resource-based view (RBV), SMEs need to utilize their available assets, including the right leadership style and innovative initiatives, to create a competitive pursuit of sustainability performance. An effective leadership style should be adaptable and flexible, manifesting in different scenarios of varying leadership behaviors. Meanwhile, innovation capital is a valuable asset that may help businesses create value in today's economy and encourage employees to be more creative. However, there has been little empirical research on the impact of leadership styles and innovative capital on sustainability performance from the emerging economies perspective. Hence, this study aimed to test the relationship between innovation capital, leadership styles, and sustainability performance of SMEs. Data were collected from 111 SMEs in Malaysia and analyzed using IBM SPSS. The results revealed that leadership styles and innovation capital have significant positive relationships with sustainability performance. This study contributes to the literature on the sustainability performance of SMEs and helps leaders strategize the appropriate leadership approaches and innovation capital to achieve sustainable performance.